High-Performance Liquid Chromatography with Diode-Array Detector for Screening of Carbamate Insecticide Residues in Vegetable Samples Using QuEChERS Extraction - Khoomsab , Ruchira; Chumanee, Saowapa (YRU Journal of Science and Technology, 2023)
Aldicarb, carbofuran, methomyl and oxamyl are carbamates insecticides. They are highly toxic and inhibit the enzyme activity of acetylcholinesterase (AChE); therefore, high residual carbamate contents in vegetables may affect consumer health. This research aimed to determine for screening of 4 carbamate residues by high-performance liquid chromatography with a diode array detector using QuEChERS extraction and clean-up purification with dispersive solid phase extraction. The chromatographic separation was performed on the C18 column using gradient elution by water and methanol at a 1 mL/min flow rate. The column temperature was controlled at 40 °C. The injection volume was 10 µL. The good linearity over a range of the concentration 0.04-2.50 mg/kg (r2>0.995). The limit of quantification was 0.05-0.07 mg/kg. Accuracy was expressed as a percentage recovery in the range of 79.25-118.57, and the precision was described as a HORRAT value of no more than 2. The method was applied for screening six vegetables, including kale, cabbage, Chinese cabbage, bog choy, green onion and chili which investigated each type for five samples, and the total conclusion was 30 samples. The scanning showed that the pesticide residues in vegetables exceeded pesticide residues, and oxamyl content was 0.15 and 0.17-0.30 mg/kg in green onion and chili, respectively. A methomyl content of 0.17 mg/kg was found in kale and green onion, and carbofuran was 0.40-0.70 mg/kg in chili.